1985
DOI: 10.1139/z85-383
|View full text |Cite
|
Sign up to set email alerts
|

Chronology, distribution, and sizes of larval fish sampled by light traps in macrophytic Chemung Lake

Abstract: Light traps were used to assess larval abundance and chronology of appearance in Chemung Lake in 1982. Eleven of 21 resident species were captured, totalling 7234 individuals. The most abundant were yellow perch (2809), Iowa darter (2571), pumpkinseed sunfish (1288), bluntnose minnow (200), and carp (123). Iowa darter and pumpkinseed were taken only as prolarvae (yolk-sac larvae) and postlarvae, but yellow perch, from 5 to 33 mm total length, were attracted. Common carp and bluntnose minnow entered traps almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Gregory & Powles (1988) compared light traps with a high speed plankton net, and found that the light traps provided more representative size-frequency distributions of larval fishes than the net In contrast to the present study, they found that the light traps sampled smaller larvae more successfully than the plankton net. This descrepancy may be due to differences in trap design, as the trap used by both Faber (1981) and Gregory & Powles (1985, 1988 was a small, l-chamber design compared to the larger, 3-chambered trap used here. Alternatively, there may be a qualitative difference in the responses by larval fishes to light in the 2 systems.…”
Section: Discussionmentioning
confidence: 87%
“…Gregory & Powles (1988) compared light traps with a high speed plankton net, and found that the light traps provided more representative size-frequency distributions of larval fishes than the net In contrast to the present study, they found that the light traps sampled smaller larvae more successfully than the plankton net. This descrepancy may be due to differences in trap design, as the trap used by both Faber (1981) and Gregory & Powles (1985, 1988 was a small, l-chamber design compared to the larger, 3-chambered trap used here. Alternatively, there may be a qualitative difference in the responses by larval fishes to light in the 2 systems.…”
Section: Discussionmentioning
confidence: 87%
“…While this pattern rnay be the result of a real difference in abundance between 1un.ar phases, the efficiency of both sampling methods has been linked to light intensity. Avoidance of plankton nets is greater with increased light intensity (Thayer et al 1983, Brander & Thompson 1989, and the catch of light traps has been found to be negatively correlated with moon illumination (Gregory & Powles 1985). Therefore, it would be expected that both sampling methods would capture fewer fish larvae dunng a full moon than during a new moon regardless of the relative abundance of the larvae during the different lunar phases.…”
Section: Newmentioning
confidence: 99%
“…Therefore, their success depends on the ability of larvae to See a light, to swim towards it and enter an illuminated enclosure (Brogan 1994), all of which may change during ontogeny (Bulkowski & Meade 1983) or with light intensity and wavelength (Gehrke 1994). It is generally accepted that light traps are both species-and size-selective (Gregory & Powles 1985, 1988, Doherty 1987, Thorrold 1992, 1993, Choat et al 1993, Brogan 1994 and, therefore, it is necessary to determine the sampling properties of light traps before incorporating them into a sampling design.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, invertebrates often form linkages between algal and detrital resources and higher trophic levels such as fish (Vadeboncoeur et al, 2002). We chose to examine edge effects on larval fish assemblages because the majority of Great Lake fish species utilize coastal wetlands at some point in their life (Jude and Pappas, 1992), either as spawning and nursery habitat (Gregory and Powles, 1985;Höök et al, 2001) or for habitat as adults (Jude and Pappas, 1992;Uzarski et al, 2005). Furthermore, the larval stage is critical for fish recruitment and larval fish are highly vulnerable to abiotic stress, predation, and food scarcity (Breitburg et al, 1999;Rose, 2000).…”
Section: Introductionmentioning
confidence: 99%